Infiltrative cardiac lymphoma with tricuspid valve involvement in a young man - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (Baishideng Publishing Group Co., 2014)
Cardiac metastases are among the topics with limited systematic review. Theoretically, the heart can be infiltrated by any malignancy with the ability to spread to distant to have a predilection for the heart, but some do metastasize more often than others, for example, melanoma and primary mediastinal tumors. We report a case od cardiac metastasis from a diffuse large B cell lymphoma in a young man. The peculiarity of this case is that besides the involvement of right ventricle and atrium, the tricuspid valve was also infiltrated. Valvular metastasis is rarely reported in the medical literature.